Risk Factors for Incident Dementia Among Older Cubans - Geeske Peeters; Geeske Peeters; Arianna Almirall Sanchez; Arianna Almirall Sanchez; Jorge Llibre Guerra; Jorge Llibre Guerra; Jorge Llibre Guerra; Brian Lawlor; Brian Lawlor; Brian Lawlor; Rose Anne Kenny; Rose Anne Kenny; et al. (Frontiers in Public Health, 2020)
Introduction: Little is known about risk factors of dementia in Latin American countries. We aimed to identify socio–demographic, health and lifestyle risk factors of incident dementia in Cuban older adults.Methods: Data were from 1,846 participants in the Cuban cohort of the 10/66 Dementia Research Group. Participants completed questionnaires, health examinations, and cognitive tests at baseline (2003–2006) and 4.5 years later (2007–2010). Associations between risk factors (baseline) and incident dementia (follow-up) were examined using logistic regression.Results: Just over 9% of participants developed dementia. Overall, older age and low physical activity were associated with incident dementia. In those 65–74 years of age, depression, stroke and low physical activity were associated with incident dementia. In those ≥75 years of age, low physical activity, never eating fish, and smoking were associated with incident dementia.Conclusions: Modifiable lifestyle factors play an important role in developing dementia in Cuban older adults. This knowledge opens up opportunities for preventive strategies.